Genotipificación de cepas de Listería monocytogenes aisladas de leche cruda de diferentes ganaderías de Lima mediante el ADN polimórfico amplificado al azar - Estrada-Ramos, Odalis (2004)
In the present study it was determined the genetic variability of Listería monocytogenes strains ísolated of raw milk from 11 dairy farms that sell this nutritional product in Lima. 250 units of sample equivalent to 50 raw milk samples were taken accordíng to FDA rules and they were streaked on the spedfic Oxford and Palcam media. L. monocytogenes was isolated in 8% (4/50) samples, 2 of Puente Piedra and 2 of Lurin. In 4% (2/50) of the samples was got Listeria spp. By positive sample 4 colonies were taken obtaining a total of 16 L. momocytogenes isolates, these were identified by biochemical tests and the polymerase chain reaction. L. monocytogenes strains were genotyping by the technique of the Random Amplified Polimorphíc DNA (RAPD) using 10 primers of arbitrary sequence. The RAPD protiles were very homogenous in the 16 isolates, generating only three genotypes named I,II and III to which belong 4, 10 and 6 isolates respectively, similar genotypes were obtained in L. monocytogenes strains coming from clinícal samples of humans. The 62,5 % (10/16) of L. monocytogenes strains isolated of raw milk of dairy farms from Lima are grouped by RAPD technique in genotype II.